Bi-containing Electrolyte Enables Robust and Li Ion Conductive Solid Electrolyte Interphase for Advanced Lithium Metal Anodes - Cui, Yongliang; Liu, Sufu; Liu, Bo; Wang, Donghuang; Zhong, Yu; Zhang, Xuqing; Wang, Xiuli; Xia, Xinhui; Gu, Changdong; Tu, Jiangping (Frontiers in Chemistry, 2020)
The notorious lithium dendrite growth, causing the safety concern, hinders the practical application of high-capacity Li metal anodes for rechargeable batteries. Here, a robust and highly ionic conductive solid electrolyte interphase (SEI) layer to protect Li metal anode is in-situ constructed by introducing trace additive of tetrapotassium heptaiodobismuthate (K4BiI7) into electrolyte. The K4BiI7-added electrolyte enables Li metal anode to display a stable cycling for over 600 cycles at 1.0 mA cm−2/1.0 mAh cm−2 and over 400 cycles at 5.0 mA cm−2/5.0 mAh cm−2. In situ optical microscopy observations also conform the suppression of Li dendrites at high current density. Moreover, the in-situ SEI layer modified Li anode exhibits an average Coulombic efficiency of 99.57% and less Li dendrite growth. The Li-S full sells with the modified electrolyte also show improved electrochemical performance. This research provides a cost-efficient method to achieve a highly ionic conductive and stable SEI layer toward advanced Li metal anodes.